Automatic modic changes classification in spinal MRI - Jamaludin, A; Kadir, T; Zisserman, A (Springer, 2016)
This paper describes a novel automatic system for Modic changes classification of vertebral endplates. Modic changes are classes of vertebral degenerations visible as intensity variations in magnetic resonance images (MRI). The system operates on T1 and T2 MRI. We introduce three main novelties: 1. a vertebrae alignment scheme via precise bounding boxes obtained through corner localisation, 2. vertebral endplate classification in three dimensions, and 3. Modic changes classification. The system was trained and validated using a large dataset of 785 patients, containing MRIs sourced from a wide range of acquisition protocols. The proposed system achieved 87.8 % classification accuracy on our dataset.